A Case Study of Undergraduate Students Computer Self-Efficacy from Rural Areas - Thinakaran, Rajermani; Ali, Rosmah; Nor Al-Ashekin Wan Husin, Wan (International Journal of Engineering and Technology, 2018)
In studentsâ€™ learning process, self-efficacy plays an important part. In Malaysia, there are a number of researches on studentsâ€™ self-efficacy. However, none of the studies focuses on undergraduate studentsâ€™ computer self-efficacy from the rural areas. This article presents a quantitative research on undergraduate studentsâ€™ perceived computer self-efficacy. A total of 128 first semester undergraduate students participated in the survey, employing a 27-item questionnaire measuring computer self-efficacy. The items were pilot-tested before being administered to the respondents. Outcome of the research show that computer self-efficacy level is high for basic and advanced skills. The result of the research shows that rural community has accepted the ICT as part of their lifestyle.Â Â Â